Analisis Aplikasi Diskusi Online Berbasis Mobile Menggunakan Metode Design Thinking - Kurnia Amanda, Destiara; Fikry, Muhammad; Yunizar, Zara (LPPM Universitas Mulia, 2025)
The advancement of information technology has accelerated digital transformation in education, including in the area of thesis supervision. However, there remains a lack of digital platforms specifically designed to support interactive communication between students and academic advisors. This research introduces Boardify, a mobile-based application developed to enhance the thesis consultation process for Informatics Engineering students. The study adopts the Design Thinking methodology, comprising five stages: empathize, define, ideate, prototype, and test. Data were obtained through observation and literature analysis, which then informed the creation of user personas, idea development, and user interface design. The application was evaluated using the System Usability Scale (SUS). Testing involving 55 participants resulted in an average SUS score of 75.6, which falls under the “acceptable” category. Validity and reliability tests also confirmed that the questionnaire items were statistically sound. These results demonstrate that Boardify delivers a positive user experience and improves the efficiency of online thesis consultation. The study contributes to the field of educational technology by offering a user-centered mobile consultation solution for academic settings, and opens up opportunities for future research in integrating artificial intelligence or learning analytics features.